Periorbital Entrapment in a Minimally Displaced Medial Wall Fracture. (7th October 2020) - Hwang, Kun
I experienced periorbital entrapment in a minimally displaced medial wall fracture. An 18-year male was hit in the left eye by a fist. He had decreased horizontal ocular motility with pain. Exophthalmometry of both eyes were same. Computed tomography (CT) demonstrated a minimally displaced medial wall fracture with herniation of orbital fat. Decreased horizontal ocular motility and pain persisted until the fifth post-trauma day. On exploration, entrapped soft tissue was found and dissected from the fractured site, but the bony displacement was minimal. After release, the forced duction test became normal and postoperative CT demonstrated reduced herniated orbital fat. In cases of a minimally displaced medial orbital wall fracture, if the patient feels pain while gazing horizontally, precise inspection of the CT scan is needed. If the pain persists for several days, despite the absence of diplopia, periorbital entrapment should be suspected and exploration can be considered.